Thermal humid treatment of walnuts as potential preventive measure against fungal contamination of chocolate confectionery fillings. (March 2017) - De Clercq, Nikki; Van Coillie, Els; Horemans, Benjamin; Duquenne, Barbara; Vandekerckhove, Marjolein; Vlaemynck, Geertrui; De Meulenaer, Bruno; Devlieghere, Frank
Abstract: Nuts are a common ingredient of confectionery fillings and a potential source of xerophilic fungal contamination. The present study investigated some preventive measures against fungal contaminants of chocolate confectionery fillings that are introduced by nuts. Microbiological analysis of the fungal load on a variety of nuts and their corresponding nut-based fillings indicated that walnuts, and the fillings in which they were used, were highly contaminated (>2.5 log10 CFU/g). The effect of dry and humid heating with various heating and drying cycle times was tested on walnuts. Humid heating for 3 min at 75–80 °C completely eliminated the initial fungal load, while dry heating did not induce any measurable change. According to sensorial analysis, humid heated and unprocessed walnuts tasted significantly different, with a slight indication of preference for the heated walnuts. These findings propose a thermal humid treatment as a possible solution to decontaminate walnuts. Moreover, hexanal analysis of walnuts demonstrated humid treatment to increase the oxidative stability of walnuts. This may result in a possible delayed onset of rancidity during storage, which is an additional advantage in terms of product shelf life. Highlights: Walnuts are a source of xerophilic fungal contamination of confectionery fillings. Humid heat-treatment of walnuts completely eliminates initial fungal contamination. Humid heat-treatment of walnuts increases oxidative stability during storage.